A Review of Traditional Chinese Medicine, Buyang Huanwu Decoction for the Treatment of Cerebral Small Vessel Disease - Sun, Liying; Ye, Xuhui; Wang, Linlin; Yu, Junping; Wu, Yan; Wang, Minpeng; Dai, Lihua (Frontiers in Neuroscience, 2022)
Cerebral small vessel disease (CSVD) is often referred to as “collaterals disease” in traditional Chinese medicine (TCM), and commonly includes ischemic and hemorrhagic CSVD. TCM has a long history of treating CSVD and has demonstrated unique efficacy. Buyang Huanwu Decoction (BHD) is a classical TCM formula that has been used for the prevention and treatment of stroke for hundreds of years. BHD exerts its therapeutic effects on CSVD through a variety of mechanisms. In this review, the clinical and animal studies on BHD and CSVD were systematically introduced. In addition, the pharmacological mechanisms, active components, and clinical applications of BHD in the treatment of CSVD were reviewed. We believe that an in-depth understanding of BHD, its pharmacological mechanism, disease-drug interaction, and other aspects will help in laying the foundation for its development as a new therapeutic strategy for the treatment of CSVD.